‘I am Duchess of Malfi still’: A Review of The Duchess of Malfi, directed by Maria Aberg, The Royal Shakespeare Company (Swan Theatre, Stratford-Upon-Avon, 2018) - Jyotsna G. Singh (Sillages Critiques)
A Review of a performance of The Duchess of Malfi, directed by Maria Aberg for the Royal Shakespeare Company (Swan Theatre, Stratford-Upon-Avon, 10 July 2018)